THE CONCEPTUALIZATION OF LOVE IN ENGLISH LITERATURE (Universal International Scientific Journal, 2026)
This paper investigates the conceptualization of love in English literary discoursewithin the framework of Conceptual Metaphor Theory. It argues that love, as an abstract emotionaldomain, is systematically structured through embodied source domains that shape its representation inliterature. Drawing on the works of William Shakespeare and Jane Austen, the study examines howmetaphorical models such as LOVE IS FIRE, LOVE IS WAR, and LOVE IS A JOURNEY organizenarrative meaning and construct distinct literary worldviews. The analysis demonstrates thatShakespeare conceptualizes love as intense and conflict-driven, foregrounding passion, instability, andemotional risk, whereas Austen presents love as a gradual process of development and moraltransformation. These differences reveal how conceptual metaphors function as cognitive frameworksrather than decorative linguistic devices. The findings suggest that metaphor plays a fundamental rolein shaping literary representations of romantic experience and reflects broader cultural patterns ofunderstanding emotion in English literary tradition.
Keywords: conceptual metaphor; conceptualization of love; English literary discourse